Energy metabolism of Heliobacterium modesticaldum during phototrophic and chemotrophic growth - Blankenship Robert E; Yue Hai; Tang Kuo-Hsiang (BMC Microbiology, 2010)
Abstract Background Heliobacterium modesticaldum is a gram-positive nitrogen-fixing phototrophic bacterium that can grow either photoheterotrophically or chemotrophically but not photoautotrophically. Surprisingly, this organism is lacking only one gene for the complete reverse tricarboxylic acid (rTCA) cycle required for autotrophic carbon fixation. Along with the genomic information reported recently, we use multiple experimental approaches in this report to address questions regarding energy metabolic pathways in darkness, CO2 fixation, sugar assimilation and acetate metabolism. Results We present the first experimental evidence that D-ribose, D-fructose and D-glucose can be photoassimilated by H. modesticaldum as sole carbon sources in newly developed defined growth medium. Also, we confirm two non-autotrophic CO2-fixation pathways utilized by H. modesticaldum: reactions catalyzed by pyruvate:ferredoxin oxidoreductase and phosphoenolpyruvate carboxykinase, and report acetate excretion during phototrophic and chemotrophic growth. Further, genes responsible for pyruvate fermentation, which provides reducing power for nitrogen assimilation, carbon metabolism and hydrogen production, are either active or up-regulated during chemotrophic growth. The discovery of ferredoxin-NADP+ oxidoreductase (FNR) activity in cell extracts provides the reducing power required for carbon and nitrogen metabolisms. Moreover, we show that photosynthetic pigments are produced by H. modesticaldum during the chemotrophic growth, and demonstrate that H. modesticaldum performs nitrogen fixation during both phototrophic and chemotrophic growth. Conclusion Collectively, this report represents the first comprehensive studies for energy metabolism in heliobacteria, which have the simplest known photosynthetic machinery among the entire photosynthetic organisms. Additionally, our studies provide new and essential insights, as well as broaden current knowledge, on the energy metabolism of the thermophilic phototrophic bacterium H. modesticaldum during phototrophic and chemotrophic growth.